Auditing cases - Knaap, Michael C. (Australia : South-Western Cengage Learing, 2011)
The book is an innovative and collaborative global development process designed to engage students and deliver content and auditing cases with global relevance.
Includes index (International edition)
uaj 04/12/2013
Loan
Keywords: Management services; Accounting -- Cases; Auditing -- Cases